{12-(-5+9)²-[+5-(-2+13][zero aqui em cima´´]-(-5+3)}
fatimacmarconi:
não dá para entender
Respostas
respondido por:
35
{12-(-5+9)²-[+5-(-2+13)⁰-(-5+3)} =
= { 12 - (4)² - [+ 5 - 1 - ( - 2)]} =
= { 12 - 16 - [ 4 +2 ]} =
={ -4 - 6} =
= - 10
Espero ter ajudado, bons estudos. Abraços
= { 12 - (4)² - [+ 5 - 1 - ( - 2)]} =
= { 12 - 16 - [ 4 +2 ]} =
={ -4 - 6} =
= - 10
Espero ter ajudado, bons estudos. Abraços
respondido por:
18
{12-(-5+9)²-[+5-(-2+13)[elevado a zero]-(-5+3)}
={12-(4)²-1-(-2)}
=12-16-1+2
=-3
={12-(4)²-1-(-2)}
=12-16-1+2
=-3
Perguntas similares
7 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás